New economy in Europe - reality or mirage? - Antje Stobbe (Deutsche Bank Research, 2001)
From a macroeconomic perspective the term "new economy" describes a phenomenon of persistent strong and low-inflation growth due to the large diffusion of information and communication technologies (ICT). This paper looks into Europe's position with respect to the new-economy phenomenon. Section III classifies the internet as a new general purpose technology (GPT). The prerequisites for the structural change induced by the internet on the micro-level are analysed in Section IV which compares the diffusion of ICT in various European countries. Section V presents findings of several empirical studies on productivity growth in Europe which look into the relation between ICT spending and labour productivity growth. Finally, the paper analyses determinants of total factor productivity growth which are of special importance in Europe.
Keywords: O47; P52; 330; new economy; productivity growth; ICT; general purpose technology; Internet; Informationstechnik; Produktivität; Wirtschaftswachstum; EU-Staaten; Westeuropa; New Economy